Ceraunus Blue Butterfly, Hemiargus ceraunus (Fabricius) (Insecta: Lepidoptera: Lycaenidae) - Jaret C. Daniels (EDIS)
EENY-425, a 2-page illustrated fact sheet by Jaret C. Daniels, is part of the Featured Creatures collection. It describes this Neotropical butterfly common in open sunny habitats in the southern U.S. — its distribution, description, life cycle and hosts. Includes selected references. Published by the UF Department of Entomology and Nematology, February 2009.